2013
DOI: 10.1097/cco.0b013e32835ff3e3
|View full text |Cite
|
Sign up to set email alerts
|

Testicular germ cell tumors

Abstract: Preclinical and clinical studies continue to enhance our insights into the complex biology of TGCTs, and are helping to further refine risk stratification and optimize treatment of patients with TGCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…About half of germ cell tumors of the testis are seminomas. Metastatic seminoma is the paradigm of a curable cancer and the cure rate has now attained 95%, with extrapulmonary visceral metastases being the main identified prognostic factor [1, 2]. The optimal postchemotherapy management of patients with seminoma has been widely debated.…”
Section: Introductionmentioning
confidence: 99%
“…About half of germ cell tumors of the testis are seminomas. Metastatic seminoma is the paradigm of a curable cancer and the cure rate has now attained 95%, with extrapulmonary visceral metastases being the main identified prognostic factor [1, 2]. The optimal postchemotherapy management of patients with seminoma has been widely debated.…”
Section: Introductionmentioning
confidence: 99%
“…TGCT are known to be related to mutations in several genes including KITLG , SPRY4 , BAK1 , TERT , DMRT1 and ATF7IP [39]. Detection of these malignant cells on the protein level can be achieved by showing positive expression mainly for POU5F1, PLAP, KIT, TFAP2C/AP-2γ and NANOG [25].…”
Section: Reasons For Failure Of Human Male Germ Cell Developmentmentioning
confidence: 99%
“…It was demonstrated that 22.7% of patients with undescended testes had a positive family history, compared to 7.5% of controls,76 with a calculated increased risk factor of cryptorchidism in newborn males of 6.9 if a brother is affected and 4.6 if the father is affected. The genes that control the proper development of the gubernaculum and testicular descent are INSL3 , the INSL3 receptor relaxin/insulin-like family peptide receptor 2 (RXFP2) , luteinizing hormone receptor and other genes involved in the regulation of the biosynthesis and/or action of androgens.…”
Section: Role Of the Genetic Background Environment And Lifestyle Inmentioning
confidence: 99%
“…Germ cell tumors (GCTs) are the most common malignancy in men between 15 and 34 years of age76 and account for 95% of testicular cancers. In 2011, Rosen et al 94.…”
Section: Role Of the Genetic Background Environment And Lifestyle Inmentioning
confidence: 99%